Activating life course policy: Social assistance and health insurance in Germany - Uwe Schwarze; Renate Niedermeier; Petra Buhr (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2003)
This paper builds on results from the Special Collaborative Centre 186 'Status Passages and Risks in the Life Course' at the University of Bremen and deals with changes in the principles of regulation and intervention within two different institutions of the welfare state: Social Assistance and Health Insurance. The empirical findings are based on expert interviews conducted at two points in time in the 1990s. We find that the traditionally differing structural principles of both systems have been supplemented with new principles of regulation and strategies of intervention in the observation period. Examples are a loss in importance of passive monetary transfers and a new emphasis on personal aid as well as orientation on 'time and action'. Thus Social Assistance and Health Insurance obviously converge towards a new model of intervention which we can call 'activating life course policy'. – – In dem vorliegenden Papier, das im Kontext des Sonderforschungsbereichs 'Statuspassagen und Risikolagen im Lebensverlauf' entstanden ist, werden Veränderungen der Steuerungs- und Interventionsmuster in zwei Systemen der sozialen Sicherung untersucht, die sich entlang unterschiedlicher Strukturprinzipien entwickelt haben: Sozialhilfe und Gesetzliche Krankenversicherung. Die Ergebnisse beruhen insbesondere auf Interviews mit Experten aus der Sozial- und Gesundheitsverwaltung zu zwei verschiedenen Erhebungszeitpunkten in den 1990er Jahren. Im Untersuchungszeitraum läßt sich in beiden Systemen eine Abkehr von passiven, auf Geldleistungen ausgerichteten Interventionsstrategien und ein Bedeutungszuwachs von personenbezogenen Dienstleistungen und stärker handlungs- und verlaufsbezogenen Orientierungen zeigen. Diese Entwicklung kann als institutionelle Annäherung beider Systeme unter dem 'Dach' einer stärker aktivierenden Lebenslaufpolitik interpretiert werden.
Keywords: 360